2010
DOI: 10.1080/13504850903035857
|View full text |Cite
|
Sign up to set email alerts
|

Does fund manager herding vary over the business cycle?

Abstract: This article aims to explore whether business cycle has any bearing on herding by fund mangers. Using the sample of open-end mutual funds in Taiwan from January 2003 to February 2007, the main results are as follows. First, excluding the impact of business indicator, herd behaviours for balanced and growth fund managers are more significant than growth-income and aggressive-growth ones. Next, the business indicator has significantly negative influence on the herding for balanced and growth fund managers. Final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Using this metric, they examined herding behavior among US pension funds between 1985 and 1989 and found that during this period pension funds herded relatively little. Recognizing that the original LCV metric may suffer from few shortcomings, Wylie (2005), Andreu et al (2009), and Huang et al (2010) modified the metric and analyzed the herd behavior among pension and mutual fund managers in different international markets. All three studies found that investors tend to herd in their respective markets.…”
Section: Introductionmentioning
confidence: 99%
“…Using this metric, they examined herding behavior among US pension funds between 1985 and 1989 and found that during this period pension funds herded relatively little. Recognizing that the original LCV metric may suffer from few shortcomings, Wylie (2005), Andreu et al (2009), and Huang et al (2010) modified the metric and analyzed the herd behavior among pension and mutual fund managers in different international markets. All three studies found that investors tend to herd in their respective markets.…”
Section: Introductionmentioning
confidence: 99%
“…Herding may temporarily inflate stock prices but could lead to future crashes [35]. Research suggests that herding behavior is more pronounced in actively traded hedge fund investments [36], and it is influenced by fund styles and strategies [37]. Interestingly, firm visits may mitigate herding behavior, possibly by confirming information [38].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%